Nonspecific oral immunotherapy with bacterial lysates in the prevention of recurrent urinary tract infections: mechanisms, clinical evidence and implications for physically active adults - Puchalski, Konrad; Lewowska , Maria; Labut , Bartłomiej; Kabak , Miroslav; Syska-Lamb, Barbara; Polakowska, Izabela; Pachcińska , Monika; Neumann , Wojciech; Sarolta Veer, Anna; Kępa , Adrianna (Quality in Sport, 2025)
Background. Women and older adults and patients with neurogenic lower urinary tract dysfunction experience rUTIs as a common and troublesome condition which causes pain and sleep disturbances and psychological issues and life quality deterioration and multiple antibiotic treatments. The increasing threat of antimicrobial resistance and microbiota disruption has led scientists to explore alternative preventive methods which do not involve antibiotics like OM-89 (Uro-Vaxom®) bacterial lysates. Aim. The research examines rUTIs pathogenesis and treatment limitations through an analysis of OM-89 oral bacterial lysate immunological effects and clinical data on rUTI prevention in physically active adults and athletes. Material and methods. The research team conducted a narrative review of published studies through database searches of PubMed Scopus Web of Science and Google Scholar from 1989 to 2025. The search terms used for this review included “bacterial lysate” and “OM-89” and “Uro-Vaxom” and “urinary tract infection” and “recurrent UTI” and “immunotherapy” and “mucosal immunity” and “non-antibiotic prophylaxis” and “athletes” and “physically active adults”. Results. Experimental studies show that oral bacterial lysates enhance host defence by activating antigen-presenting cells, increasing secretory IgA and systemic IgG and inducing trained immunity. Conclusions. The protected non-antibiotic solution OM-89 in oral bacterial lysates serves as a preventive treatment for rUTI because it strengthens host defenses instead of directly eliminating pathogens. The development of sports medicine research must establish quantitative measures for training availability and time-loss illness and performance impact while creating optimal preventive strategies for athletes.